Toll-Like Receptor 7-Targeted Therapy in Respiratory Disease - Lebold, Katie M. (Transfus Med Hemother, 2016)
Allergic asthma and allergic rhinitis are inflammatory diseases of the respiratory tract characterized by an excessive type-2 T helper cell (Th2) immune response. Toll-like receptor 7 (TLR7) is a single-stranded viral RNA receptor expressed in the airway that initiates a Th1 immune response and has garnered interest as a novel therapeutic target for treatment of allergic airway diseases. In animal models, synthetic TLR7 agonists reduce airway hyperreactivity, eosinophilic inflammation, and airway remodeling while decreasing Th2-associated cytokines. Furthermore, activation of TLR7 rapidly relaxes airway smooth muscle via production of nitric oxide. Thus, TLR7 has dual bronchodilator and anti-inflammatory effects. Two TLR7 ligands with promising pharmacologic profiles have entered clinical trials for the treatment of allergic rhinitis. Moreover, TLR7 agonists are potential antiviral therapies against respiratory viruses. TLR7 agonists enhance influenza vaccine efficacy and also reduce viral titers when given during an active airway infection. In this review, we examine the current data supporting TLR7 as a therapeutic target in allergic airway diseases.